An increase in insulin sensitivity and basal beta-cell function in diabetic subjects treated with pioglitazone in a placebo-controlled randomized study. - Wallace, T; Levy, J; Matthews, DR (2004)
AIMS: To investigate the effect of treatment with pioglitazone on beta-cell function and insulin sensitivity in Type 2 diabetes. METHODS: Thirty subjects with diet-controlled Type 2 diabetes were randomized to 3 months treatment with pioglitazone (n = 19) or placebo (n = 11). All subjects underwent basal sampling for homeostatic model assessment (HOMA), followed by an intravenous glucose tolerance test and hyperglycaemic clamp, followed by an euglycaemic hyperinsulinaemic clamp; at baseline and after treatment. RESULTS: All results are expressed as mean (sem). Pioglitazone increased basal insulin sensitivity by 24.7% (7.8) HOMA-%S vs. 2.1% (5.9) in the placebo group (P = 0.02). Stimulated insulin sensitivity, M/I, increased in the pioglitazone group compared with placebo: +15.1 (2.8) l kg(-1) min(-1) vs. +3.2 (2.9) l kg(-1) min(-1), respectively (P = 0.009). Pioglitazone increased adiponectin by 39.3 (6.3), ng/ml compared with a decrease of 0.8 (1.3) ng/ml with placebo (P = 0.00004). HOMA-%B increased with pioglitazone, +11.5% (4.8) vs. -2.0% (4.8) with placebo (P = 0.049), but there was no change in stimulated beta-cell function as determined by hyperglycaemic clamps. There was a significant reduction in the proinsulin/insulin ratio in the pioglitazone group, -0.057 (0.02) compared with placebo, +0.004 (0.02) (P = 0.03). There was a significant reduction in HbA(1c) of 0.6% (0.1) in the pioglitazone group compared with placebo (P = 0.003). There was no significant weight gain associated with pioglitazone therapy: +0.7 (sem 0.6) kg vs. +1.1 (sem 0.5) kg in placebo group (P = NS). CONCLUSIONS: Basal beta-cell function and insulin sensitivity improved following pioglitazone therapy. The improvement in proinsulin to insulin ratio suggests that beta-cells are under less stress.